THE DEVELOPMENT OF MARBLE TRADITIONAL GAME BASED-PROTOTYPE CURRICULUM - Muslihin, Heri Yusuf; Respati, Resa; Susanti, Putri Irma (Jurnal Tatsqif, 2022)
The lack of understanding of the benefits of traditional games for children's growth and development is the background of research, thus causing the extinction of traditional games from the community. In fact, traditional games have many benefits for children's growth and development, especially games played outside the home. Besides being played in the community, traditional games can also be used as learning media for children at school. However, this has not been done much because traditional games are still limited to local content where the implementation is returned to the school concern. The purpose of this study was to develop a prototype curriculum based on the traditional game of marbles to develop the growth and development of early childhood. This study uses a qualitative approach and the research method used is Design Based Research (DBR). The research instrument is the researcher and the participant. The steps taken in data analysis in this study were data reduction (organizing data), data display (making detailed descriptions), and conclusion drawing/verification (interpreting and drawing conclusions). The result of this research is the development of learning tools in the form of RPPH (daily lesson implementation plan) based on the traditional game of marbles.